Mechanical integration of plant cells and plants - Wojtaszek, Przemyslaw; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
Chemical reactions and interactions between molecules are commonly considered the basis of life, and thus the biochemical nature of cells and organisms is relatively well recognized. Research conducted in recent years, however, increasingly indicates that physical forces profoundly affect the functioning of life at all levels of its organization. To detect and to respond to such forces, plant cells and plants need to be structured mechanically. This volume focuses on mechanical aspects of plant life. It starts with a consideration of the mechanical integration of supracellular structures and mechanical properties of cellular building blocks to show how the structural integrity of plant cells is achieved and maintained during growth and development. The following chapters reveal how the functioning of integrated plant cells contributes to the mechanical integration of plants, and how the latter are able to detect physical stimuli and to reorganize their own cells in response to them. The mechanical aspects of plant responses to stresses are also presented. Finally, all these aspects are placed in an evolutionary context.
Introduction: Tensegral World of Plants -- Micromechanics of Cell Walls -- Mechanics of the Cytoskeleton -- Intracellular Movement. Integration at the Cellular Level as Reflected in the Organization of Organelle Movements -- Generating a Cellular Protuberance. Mechanics of Tip Growth -- Mechanics of the Meristems -- Mechanical Force Responses of Plant Cells and Plants -- Mechanical Aspects of Gravity-Controlled Growth, Development and Morphogenesis -- Osmosensing -- Plants as Mechano-Osmotic Transducers -- Integrative Mechanobiology of Growth and Architectural Development in Fluctuating Mechanical Environments -- Hydraulics of Vascular Water Transport -- MicroRNAs and Mechanical Stress.
College of Science Library has electronic copy. Kindly send us a message through cslib@science.upd.edu.ph using your UP mail for the copy of this material.
Electronic reproduction.
Keywords: Plant cellular control mechanisms; Plant cell interaction; Electronic books